1990
DOI: 10.1080/00223980.1990.10543258
|View full text |Cite
|
Sign up to set email alerts
|

Color Preference and Food Choice Among Children

Abstract: The effects of color on children's food choices were investigated. Subjects were 120 children who were equally distributed among each of the combinations of age (5 vs. 9 years old), sex (male vs. female), food type (3 types of candies), and color (red, green, yellow, and orange) in a counterbalanced, factorial, analysis-of-variance design with repeated measures on subjects. A significant main effect for color indicated that children preferred foods that were red, green, orange, and yellow, in that order. Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
3

Year Published

1997
1997
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 12 publications
3
43
0
3
Order By: Relevance
“…There was no significant difference in liking of green and brown, p ϭ .114. This main effect replicates the overall preference for the color blue demonstrated by past research (Dittmar, 2001;Lind, 1994;Silver & Ferrante, 1995;Silver et al, 1988;Walsh et al, 1990). There was no interaction between the name given (generic or fancy) and the color (blue, brown, and green) itself F(2, 190) ϭ 1.72, p ϭ .18.…”
Section: Fancy-name Effectsupporting
confidence: 58%
See 1 more Smart Citation
“…There was no significant difference in liking of green and brown, p ϭ .114. This main effect replicates the overall preference for the color blue demonstrated by past research (Dittmar, 2001;Lind, 1994;Silver & Ferrante, 1995;Silver et al, 1988;Walsh et al, 1990). There was no interaction between the name given (generic or fancy) and the color (blue, brown, and green) itself F(2, 190) ϭ 1.72, p ϭ .18.…”
Section: Fancy-name Effectsupporting
confidence: 58%
“…231-235). Additional research on primary colors has shown a strong preference (or liking) for the color blue and a trend to dislike the color yellow (see Dittmar, 2001;Lind, 1994;Silver & Ferrante, 1995;Silver et al, 1988;Walsh et al, 1990). Thus, color seems to be very influential in people's memories and preferences.…”
Section: Color Perceptionmentioning
confidence: 99%
“…This finding also gives credence to Ptichford and Mullen (1990), who found that children prefer brown and gray significantly less than basic colours. Walsh et al (1990) also postulate that children preferred foods that were red, green, orange and yellow, in that order. This partly supports the result of these findings.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, for example, the toast was more familiar to students than the donuts because toast is offered daily while donuts are rarely, if ever, offered. The cold cereal option was another instance of a familiar school breakfast offering that was made more attractive by individually wrapped boxes, rather than the bulk cereal typically served (18). Eggs, on the other hand, are rarely if ever served to students for school breakfast.…”
Section: Discussionmentioning
confidence: 99%